CO-DOPING Y, Nd, AND Sm ANALYSIS WITH SOL-GEL SYNTHESIS METHOD IN GADOLINIUM DOPED CERIA (GDC) SOLID ELECTROLITE SYSTEM FOR INTERMEDIATE TEMPERATURE SOLID OXIDE FUEL CELL (IT-SOFC) - Fath Mamerda, Widya
Solid Oxide Fuel Cell - SOFC is an energy conversion system that is important because it has high efficiency, modular design and environmentally friendly. The main problem in SOFC is the high operating temperature. Conventional SOFC has an operating temperature of around 800-1000?C . The concern at this time is to reduce the operating temperature of SOFC to an intermediate temperature of 600- 800?C and increase to long-term stability. In an effort to reduce the operating temperature, an increase in ionic conductivity is needed by modifying the process, microstructure, and composition. In this study, a solid electrolyte system based on Gadolinium Doping Cerium (GDC) was made with the addition of co-dopants Y, Nd and Sm. The compositions of each solid electrolyte are Ce0.7Gd0.2YxO1,9 , Ce0,9Gd0,075NdxO1,9 and Ce0,85Gd0,05SmxO2-x with x is variations of 0%; 2,5%; 5%; and 7,5 %. Powder preparation is done by the sol-gel method which passes the stages of mixing, drying and calcination. Furthermore, the powder produced was compacted with a force of 40 kN so that the resulting green pellet is approximately 1 cm in diameter. The sintering was then carried out at a temperature variation of 1000?C,1200?C and 1400?C with a holding time of 4 hours. The dimensions and mass of each sample before and after sintering were measured to determine the value of the relative density and densification of each sample. Electrochemical Impedance Spectroscopy (EIS) tests were carried out using Potentiostat-Gamry Instrument Ref. 600 in the operating temperature range of 500-700?C with a temperature difference of 50?C per data collection. Data from EIS test results were analyzed to determine the electrical characteristics of each sample. Besides that, sample characterization was also carried out using XRD and SEM . The electrical circuit model equivalent to all samples are generally consisting of LRg- (Rgb / CPEgb) - (Rp3 / CPE3), where L is an inductor, R is a resistor, and CPE is a phase element constant. Percentage of densification will increase, grain and grain boundaries resistances decreased by increasing sintering temperature. The highest densification value of each co-dopant addition was reached at 1400oC by sample with the addition of 7,5% Y, 2,5% Nd, and 5% Sm, which were 52,44%, 63,93% and 64,10% respectively. Ionic conductivity increased and the activation energy decreased with increasing sintering temperature. The highest ionic conductivity was produced by the sample with the addition of 5% Sm at 1400oC sintering temperature of 2.75 x 10-2 S/cm and the lowest activation energy was achieved by the sample with 2.5% Nd addition at 1400oC sintering temperature of 0.167 eV.